The Discourse of an Aboriginal Fishery - Adlam, Robert G. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2000)
The present paper draws on a collection of recorded interviews undertaken over the course of three summers of fieldwork among Aboriginal fishers of the Miramichi river of northern New Brunswick. Here particular attention is given to the discourse of these fishers, taken to mean their ‘talk’ about the fishery. Indeed it is through such discourses that the fishery is at once created and transformed reflecting in part past practice based on family gill net operations, and in more recent years, the experience of a highly regulated and waged trap net operation. It is hoped that the present paper will contribute to our understanding of the discursive construction of economy especially as this relates to the practices of aboriginal riverine fishers.